Violence: a glossary - Rutherford, Alison (BMJ Group, 2007)
Violence has been explicitly identified as a significant public health problem. This glossary clarifies widely used definitions and concepts of violence within the public health field, building on those promoted through the 2002 World Report on Violence and Health. We provide definitions and concepts that can be usefully applied to identify points for public health intervention to prevent the social and health impacts of violence.